Rare bird documentation form for Lesser Black-backed Gull at Coralville Reservoir, 1993 - Bendorf, Carl J.et al (1993)
Rare bird documentation form for a Lesser Black-backed Gull at Coralville Reservoir in Johnson County, IA on December 18, 1993. Epson - sheet feed